Tinjauan Normatif Implementasi Justice Collaborator Sebagai Upaya Pengungkapan Fakta Hukum Tindak Pidana Pembunuhan Berencana Dalam Putusan Nomor: 796/Pid.B/2022/Pn.Jkt.Sel - Msg, M.Saufi Satria; Muhlizar, Muhlizar; Nasution, Dian Mandayani Ananda (Universitas Medan Area, 2025)
Premeditated murder is a serious criminal offense that threatens the fundamental right to life and generates broad social implications, including fear and public unrest. The case examined in Decision Number 796/Pid.B/2022/PN.Jkt.Sel holds distinctive juridical and sociological relevance, particularly due to the involvement of law-enforcement officers as perpetrators and the crucial role of a cooperating offender (Justice Collaborator) in revealing the material truth. The presence of a Justice Collaborator introduces an important dialectic: while serving as an effective instrument in proving complex criminal cases, it simultaneously raises concerns regarding legal protection guarantees and sentencing consistency. This research employs a normative juridical method with statutory and case approaches. Primary legal sources include the Criminal Code (KUHP), the Criminal Procedure Code (KUHAP), Law No. 31 of 2014 on Witness and Victim Protection, and Supreme Court Circular Letter No. 4 of 2011, analyzed alongside doctrinal and academic literature. Findings indicate that although the Justice Collaborator mechanism has obtained normative legitimacy, its regulation remains partial and lacks systematic codification in a dedicated statute. Judicial considerations in Decision Number 796/Pid.B/2022/PN.Jkt.Sel demonstrate that the status of a Justice Collaborator is treated as a mitigating factor due to their significant contribution to uncovering material truth. Thus, the application of the Justice Collaborator scheme in premeditated murder cases not only enhances the effectiveness of criminal justice but also underscores the urgency of establishing more comprehensive and equitable legal protection mechanisms.